Design of a haptic palmar-finger feedback system for upper limb myoelectric prosthesis model PUCP-Hand - Romero, E.; Elías, D.A. (Institute of Electrical and Electronics Engineers, 2022)
This paper presents the design of a haptic palmar-finger feedback system for transradial myoelectric upper limb prosthesis that allows an amputated person to percieve the sensations related to force-gripping, object-sliding and proprioception of the prosthetic fingers. The designed system has two subsystems. A monitoring unit arranged on the prosthetic hand, and an actuation unit embedded in a bracelet around the user’s forearm. Both units have independent energizing systems and communicate wirelessly. In order to validate the design, simulations of the electronic system and finite element method (FEM) analysis of the actuation unit were carried out.
Keywords: Haptic technology; Prosthetic hand; Forearm; Computer science; Robotic hand; Finite element method; Proprioception; Engineering; Simulation; Artificial intelligence; Physical medicine and rehabilitation; Structural engineering; Anatomy; Robot; https://purl.org/pe-repo/ocde/ford#2.03.01